K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

12 tháng 7 2017

\(x^2-2x-2-2\sqrt{2x+1}=0\)

\(\Leftrightarrow x^2-2x-8-\left(2\sqrt{2x+1}-6\right)=0\)

\(\Leftrightarrow\left(x-4\right)\left(x+2\right)-\frac{4\left(2x+1\right)-36}{2\sqrt{2x+1}+6}=0\)

\(\Leftrightarrow\left(x-4\right)\left(x+2\right)-\frac{8\left(x-4\right)}{2\sqrt{2x+1}+6}=0\)

\(\Leftrightarrow\left(x-4\right)\left(x+2-\frac{8}{2\sqrt{2x+1}+6}\right)=0\)

Thấy: \(x+2-\frac{8}{2\sqrt{2x+1}+6}>0\)

\(\Rightarrow x-4=0\Rightarrow x=4\)